DETERMINANTS OF REGIONAL GOVERNMENT FINANCIAL PERFORMANCE IN INDONESIA - Febriyanti, Kur; Zulkifli, Zulkifli; Oktarida, Anggeraini (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
The importance of local governments in providing public services and supporting national development goals is growing. As a result, systematic control, assessment, and performance measurement are crucial. This analysis aims to identify factors that affect the financial performance of provincial governments in Indonesia, focusing on local government size, balancing of funds, regional expenditures, and audit results. Financial performance is assessed through the independence ratio. Utilizing secondary data from Audit Reports of Provincial Government Financial Statements from 2021 to 2023, the study covers all 34 provinces selected through purposive sampling, resulting in 102 analysis units. Multiple linear regression using EViews version 13 reveals that local government size and regional expenditures harm financial performance, while balanced funds have a significant positive effect. Moreover, audit findings do not significantly influence financial performance. The analysis shows that increasing total assets does not guarantee better financial results due to ineffective asset management. The lack of correlation between audit findings and financial performance suggests that audit reports may not reliably indicate fiscal health. Policy recommendations emphasize the importance of efficient asset management, strategic utilization of balancing funds, and effective follow-up on audit recommendations to promote accountability and fiscal sustainability.